2018
DOI: 10.1155/2018/6785741
|View full text |Cite
|
Sign up to set email alerts
|

Snacking Behaviour and Its Determinants among College-Going Students in Coastal South India

Abstract: Background Consumption of snacks in between the regular meals is a poor snacking behaviour. It is an established risk factor for several lifestyle-related disorders and has long-term effects among the younger individuals. Objectives To study the snacking behaviour and to assess their determinants among college-going students. Methods This cross-sectional study was conducted among 865 college-going students in Mangaluru. Data were collected using a pretested pro forma that was coded and analyzed using Statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 22 publications
0
28
1
4
Order By: Relevance
“…Our results showed that most of the students had less than two snacks per day, while about one-third of them had over two snacks per day, which was insignificantly higher among males. Similarly, in India, males had more frequent snacking behavior compared to females (68).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our results showed that most of the students had less than two snacks per day, while about one-third of them had over two snacks per day, which was insignificantly higher among males. Similarly, in India, males had more frequent snacking behavior compared to females (68).…”
Section: Discussionmentioning
confidence: 91%
“…Mansouri et al reported that regular breakfast consumption was inversely associated with overweight and obesity in college students (67). The students' higher tendency to skip meals might be associated with an increased risk of poor snacking behavior (68). Snacking between meals might be correlated with an increased risk of being overweight or obese (69).…”
Section: Discussionmentioning
confidence: 99%
“…We found that healthy breakfast consumers had a higher AMD. Based on our knowledge, no other study has sought this association, but studies have shown that breakfast skippers tend to have poor dietary habits overall, with an irregular snacking frequency and a high consumption of unhealthy foods and beverages [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…35 Another study conducted in southern India also reveals that a higher proportion of students with lower SES from government colleges had unhealthy snacking behavior. 42 Similarly, a scoping review study concluded that SES significantly influences the eating behavior among adolescents. Further, it also claimed that low SES is associated with unhealthy snacking behavior in adolescents.…”
Section: Discussionmentioning
confidence: 99%